PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII PADA MATA PELAJARAN PPKN DI SMP NEGERI 10 KOTA JAMBI - Husna, Febriza Laila; Salam, M.; Hakim, M. Lukman (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the effect of the Student Teams Achievement Division (STAD) Cooperative Learning Model on the Critical Thinking Ability of Class VIII Students in Civics Subject at SMP Negeri 10 Jambi City. The research method uses a quasi-experimental design research design Pretest-Posttest Control Group Design. The population in this study were all students of class VIII SMP Negeri 10 Jambi City. The sampling technique used was purposive sampling. Retrieval of research data using observation and test techniques. The data was tested by t-test and N-Gain test using SPSS 26 For windows software. The results showed that there was an influence of the Student Teams Achievement Division (STAD) Cooperative Learning Model on the Critical Thinking Ability of Class VIII Students in Civics Subject at SMP Negeri 10 Jambi City. Judging from the results of the independent t-test, namely count> ttable of 10,498> 2,004. with a df value of 54 and at a level of 5%. In the N-Gain test, the average value of the experimental class was 67.78 or 68% which was included in the quite effective category. Meanwhile, the mean or average value in the control class is 8.834 or 9% included in the ineffective category, which means that there is a significant difference between the experimental class and the control class.